Adapting brain metabolism to myelination and long‐range signal transduction. Issue 11 (6th August 2014) - Hirrlinger, Johannes; Nave, Klaus‐Armin; Matute, Carlos; Stys, Peter K.
<x xml:space="preserve">Abstract</x> In the mammalian brain, the subcortical white matter comprises long‐range axonal projections and their associated glial cells. Here, astrocytes and oligodendrocytes serve specific functions during development and throughout adult life, when they meet the metabolic needs of long fiber tracts. Within a short period of time, oligodendrocytes generate large amount of lipids, such as cholesterol, and membrane proteins for building the myelin sheaths. After myelination has been completed, a remaining function of glial metabolism is the energetic support of axonal transport and impulse propagation. Astrocytes can support axonal energy metabolism under low glucose conditions by the degradation of stored glycogen. Recently it has been recognized that the ability of glycolytic oligodendrocytes to deliver pyruvate and lactate is critical for axonal functions in vivo. In this review, we discuss the specific demands of oligodendrocytes during myelination and potential routes of metabolites between glial cells and myelinated axons. As examples, four specific metabolites are highlighted (cholesterol, glycogen, lactate, and N‐acetyl‐aspartate) that contribute to the specific functions of white matter glia. Regulatory processes are discussed that could be involved in coordinating metabolic adaptations and in providing feedback information about metabolic states. © GLIA 2014;62:1749–1761